Sponge cell reaggregation: Cellular structure and morphogenetic potencies of multicellular aggregates. Issue 2 (11th February 2016) - Lavrov, Andrey I.; Kosevich, Igor A.
ABSTRACT: Sponges (phylum Porifera) are one of the most ancient extant multicellular animals and can provide valuable insights into origin and early evolution of Metazoa. High plasticity of cell differentiations and anatomical structure is characteristic feature of sponges. Present study deals with sponge cell reaggregation after dissociation as the most outstanding case of sponge plasticity. Dynamic of cell reaggregation and structure of multicellular aggregates of three demosponge species ( Halichondria panicea (Pallas, 1766), Haliclona aquaeductus (Sсhmidt, 1862), and Halisarca dujardinii Johnston, 1842) were studied. Sponge tissue dissociation was performed mechanically. Resulting cell suspensions were cultured at 8–10°C for at least 5 days. Structure of multicellular aggregates was studied by light, transmission and scanning electron microscopy. Studied species share common stages of cell reaggregation—primary multicellular aggregates, early‐stage primmorphs and primmorphs, but the rate of reaggregation varies considerably among species. Only cells of H. dujardinii are able to reconstruct functional and viable sponge after primmorphs formation. Sponge reconstruction in this species occurs due to active cell locomotion. Development of H. aquaeductus and H. panicea cells ceases at the stages of early primmorphs and primmorphs, respectively. Development of aggregates of these species is most likely arrested due to immobility of the majority of cells inside them. However, the inability of certain sponge species to reconstruct functional and viable individuals during cell reaggregation may be not a permanent species‐specific characteristic, but depends on various factors, including the stage of the life cycle and experimental conditions. J. Exp. Zool. 9999A:XX–XX, 2016. © 2016 Wiley Periodicals, Inc.